Depression is the strongest predictor of long-term outcome in patients with chronic nonischemic heart failure - Szyguła-Jurkiewicz, Bożena; Zakliczyński, Michał; Ploch, Michał; Mościński, Mateusz; Partyka, Robert; Wojnicz, Romuald; Zembala, Marian; Poloński, Lech (Kardiochirurgia i Torakochirurgia Polska/Polish Journal of Thoracic and Cardiovascular Surgery, 2014)
Introduction : Despite advances in medicine, chronic heart failure (CHF) still remains a significant clinical problem associated with poor outcome. Aim of the study: To determine risk factors for major adverse cardiac events (MACE) in three-year follow-up in patients with CHF of nonischemic etiology. Material and methods : The prospective study included consecutive hospitalized patients with stable CHF (LVEDD > 57 mm; LVEF 6 months. Study exclusion criteria were: serious neurological and/or psychiatric diseases, steno-ses in epicardial coronary arteries in coronarography, active myocarditis confirmed by myocardial biopsy, diseases of the respiratory system with pulmonary hypertension, presence of heart defects, neoplastic or connective tissue disease, documented infectious dis-eases at least three months before inclusion in the study, diabetes, liver cirrhosis, chronic kidney disease (eGFR < 30 ml/min/1.73 m2), alcoholism, planned heart transplantation. Depression severity was assessed with the Beck and the Hamilton Scales. Depression was diagnosed based on the ICD-10 criteria. Clinical follow-up began on admission and lasted three years. Results: The analysis encompassed 199 patients aged 49 (41-54), who met the inclusion/exclusion criteria. Depression was diagnosed in 30% of the patients. Independent factors increasing the risk of MACE (death, transplantation, ventricular assist device, hospitalization) were: depression (HR: 2.26; p < 0.001), E/A index (HR: 1.31; p < 0.01), right ventricular dimension (HR: 1.06; p < 0.01), hsCRP level (HR: 1.06; p < 0.01) and alkaline phosphatase activity in blood serum (HR: 1.01; p < 0.05). Conclusions: Factors affecting 3-year outcome are: depression, right ventricular dimension, the E/A index, alkaline phospha-tase activity and the level of high-sensitivity C-reactive protein (hs-CRP).